A porous zinc(II) metal–organic framework exhibiting high sensing ability for ferric and nitroaromatics as well as photocatalytic degradation activities against organic dyes. Issue 23 (2nd December 2017) - Liu, Jianqiang; Wu, Jian; Luo, Zhidong; Li, Baohong; Singh, Amita; Abhinav, Kumar
Abstract: A NbO-type Zn(II) metal–organic framework of {[Zn2 (HL)(H2 O)2 ]∙H2 O}n (1 ) has been developed using a pentacarboxylate 2, 5-bis(3′, 5′-dicarboxylphenyl)-benzoic acid (H5 L) ligand and characterized. The single-crystal X-ray diffraction studies indicate that1 comprises free –COOH groups and Zn(II) centers bridged by four carboxylate groups to form a paddle wheel SBU which is further connected by L 5− ligands to build a 3-D porous network with two types of cages. The chemically stable MOF1 behaves as a highly selective and sensitive fluorescent chemosensor for the detection of Fe 3+ ions, 2, 4, 6-trinitrophenol (TNP), which is known to be an extremely hazardous and strong explosive. Furthermore, the photocatalytic properties of1 for degradation of methyl violet (MV) and Rhodamine B (RhB) have been explored. The possible emission quenching mechanism in the presence of nitro-aromatics (NACs) has been addressed by theoretical calculations and photocatalytic activity of1 against organic dyes has been supported using density of states (DOS) calculations. Abstract :